Integration of Ergonomics in Work System Design to Enhance Employee Performance and Well-being in the Manufacturing Sector - Taufik, Deni Ahmad (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This paper explores the integration of ergonomics into work system design to enhance employee performance and well-being in the manufacturing sector. The primary objective of this research is to identify and analyze how the application of ergonomic principles can optimize the work environment, which in turn positively impacts employee productivity and reduces work-related injuries. The research employs a qualitative approach, using in-depth interviews and observations with employees and managers from several manufacturing companies. The findings indicate that the implementation of ergonomics not only improves physical comfort but also has a positive psychological effect, such as increased job satisfaction and motivation. Additionally, ergonomic work designs have been found to reduce fatigue and injuries, thereby improving operational efficiency and lowering costs related to absenteeism and health insurance claims. This study recommends that manufacturing companies become more proactive in integrating ergonomics into their work systems to support the long-term well-being of employees. The results are expected to serve as a reference for company policies and further research on the implementation of ergonomics in industrial work environments.